Parents and Adolescents Pattern of Interpersonal Communication in The Restriction of Smartphone Usage - ., Muslim (Journal of Humanities and Social Studies, 2017)
Communication can be the media of proximity of parents and children. Parents will feel comfortable because they feel the child needs and love him. Conversely, the child will feel happy to get the attention of his parents. The development of communication technology led to a new style of communication style. Parent and child communication is no longer done face-to-face at the dinner table or in the living room. The role of interpersonal communication of parents and children began to shift since the presence of a smart tool that was created able to perform many activities.Communication patterns between adolescent boys and girls tend to be different Young men and women have different tendencies in smartphone use. Female teenagers are more dominant using social media to upload good photographs with friends or photos themselves. Young men use smartphones to play games, download songs, movies or video clips. Teenagers in Indonesia (40-50 percent) is a community of hp (smartphone) users. Teenagers use social media that includes instant messengers like LINE, Instagram, Twitter and other apps like Facebook, Youtube, Vlog and more. There are three patterns of communication that parents do in limiting the use of smartphones in adolescents. The patterns are Authoritarian communication patterns, Democratic communication patterns and Permissive Communication Patterns. Keywords: Communication Patterns, smartphones, restrictions